Metabolic Reprogramming Helps to Define Different Metastatic Tropisms in Colorectal Cancer - Montero-Calle, Ana; Gómez de Cedrón, Marta; Quijada-Freire, Adriana; Solís-Fernández, Guillermo; López-Alonso, Victoria; Espinosa-Salinas, Isabel; Peláez-García, Alberto; Fernández-Aceñero, María Jesús; Ramírez de Molina, Ana; Barderas, Rodrigo (Frontiers in Oncology, 2022)
Approximately 25% of colorectal cancer (CRC) patients experience systemic metastases, being the most frequent target organs liver and lung. Metabolic reprogramming has been recognised as one of the hallmarks of cancer. Here, metabolic and functional differences between two CRC cells with different metastatic organotropisms (metastatic KM12SM CRC cells to liver and KM12L4a to lung when injected in the spleen and in the tail vein of mice) were analysed in comparison to their parental non-metastatic isogenic KM12C cells, for a subsequent investigation of identified metabolic targets in CRC patients. Meta-analysis from proteomic and transcriptomic data deposited in databases, qPCR, WB, in vitro cell-based assays, and in vivo experiments were used to survey for metabolic alterations contributing to their different organotropism and for the subsequent analysis of identified metabolic markers in CRC patients. Although no changes on cell proliferation were observed between metastatic cells, KM12SM cells were highly dependent on oxidative phosphorylation at mitochondria, whereas KM12L4a cells were characterized by being more energetically efficient with lower basal respiration levels and a better redox management. Lipid metabolism related targets were found altered in both cell lines, including LDLR, CD36, FABP4, SCD, AGPAT1 and FASN, which were also associated with the prognosis of CRC patients. Moreover, CD36 association to lung metastatic tropism of CRC cells was validated in vivo. Altogether, our results suggest that LDLR, CD36, FABP4, SCD, FASN, LPL and APOA1 metabolic targets are associated to CRC metastatic tropism to liver or lung. These features exemplify specific metabolic adaptations for invasive cancer cells which stem at the primary tumour.